Catalytic Pyrolysis of Polyethylene with Microporous and Mesoporous Materials: Assessing Performance and Mechanistic Understanding - Minkelis, Johan H.; Hergesell, Adrian H.; Waal, Jan C.; Altink, Rinke M.; Vollmer, Ina; Weckhuysen, Bert M. (ChemSusChem, 2025)
Testing the catalytic performance for the catalytic pyrolysis of plastic waste is hampered by mass transfer limitations induced by a size mismatch between the catalyst′s pores and the bulky polymer molecules. To investigate this aspect, the catalytic behaviour of a series of microporous and mesoporous materials was assessed in the catalytic pyrolysis of polyethylene (PE). More specifically, a mesoporous material, namely sulfated zirconia (Zr(SO4)2) on SBA‐15, was synthesized to increase the pore accessibility, which reduces mass transfer limitations and thereby enables to better assess the effect of active site density on catalyst activity. To demonstrate the potential of this approach, the mesoporous SBA‐15 catalysts were compared to a series of microporous zeolite Y catalysts. Using the degradation temperature during thermogravimetric analysis (TGA) as a measure of activity, no correlation between acidity and activity was observed for microporous zeolite Y. However, depending on the Mw of PE, the reactivity of the mesoporous catalysts increased with increasing Zr(SO4)2 weight loading, showing that utilizing a mesoporous catalyst can overcome the accessibility limitations at least partially, which was further confirmed by polymer melt infiltration and in situ X–ray diffraction. Detailed product analysis revealed that more aromatics and coke deposits were produced with the more acidic zeolite Y materials. The mesoporous material remained active and structurally intact over multiple cycles and catalyses PE degradation via acid‐ and radical‐based pathways. The pore accessibility and activity have been assessed with a set of microporous and mesoporous catalyst materials for polyethylene pyrolysis. It was found that pore accessibility dominates over acidity for high‐molecular weight polyethylene conversion, thereby showcasing the need to design a new generation of more porous solid acids for the effective catalytic conversion of polyolefin waste.